Regio‐ and Stereoselective Thianthrenation of Olefins To Access Versatile Alkenyl Electrophiles. Issue 14 (3rd February 2020) - Chen, Junting; Li, Jiakun; Plutschack, Matthew B.; Berger, Florian; Ritter, Tobias
Abstract: Herein, we report a regioselective alkenyl electrophile synthesis from unactivated olefins that is based on a direct and regioselective C−H thianthrenation reaction. The selectivity is proposed to arise from an unusual inverse‐electron‐demand hetero‐Diels–Alder reaction. The alkenyl sulfonium salts can serve as electrophiles in palladium‐ and ruthenium‐catalyzed cross‐coupling reactions to make alkenyl C−C, C−Cl, C−Br, and C−SCF3 bonds with stereoretention. Abstract : The regioselective synthesis of sulfonium‐based alkenyl electrophiles was achieved directly through C−H functionalization of simple olefins. The alkenyl sulfonium salts participate in palladium‐catalyzed cross‐coupling and ruthenium‐catalyzed (pseudo)halogenation reactions.